"When you were gentiles": specters of ethnicity in Roman Corinth and Paul's Corinthian correspondence - Concannon, Cavan W. (Synkrisis: comparative approaches to early Christianity in Greco-Roman culture, 2014)
Cavan W. Concannon makes a significant contribution to Pauline studies by imagining the responses of the Corinthians to Paul's letters. Based on surviving written materials and archaeological research, this book offers a textured portrait of the ancient Corinthians with whom Paul conversed, argued, debated, and partnered, focusing on issues of ethnicity, civic identity, politics, and empire